Demystifying the Magic in Diamond Shumsher’s Seto Bagh: History Reconsidered - Neupane, Nabaraj (SCHOLARS: Journal of Arts & Humanities, 2021)
Diamond Shumsher’s masterpiece, Seto Bagh, is a significant historical novel in Nepali literature. The novel made a vibrant debut in depicting historicity in fictional prose in the Nepali context. In particular, the reconsideration of the portrayal of history from a new perspective is relevant. Traditionally, this is considered a historical realist novel. Nevertheless, magical elements are profusely used in the novel. In this study, this niche opens up avenues to re-evaluate the historicity vis-à-vis magical elements. I have adopted Maggie Ann Bowers’ and Wendy B. Faris’s notions and perspectives on the theoretical lens of magical realism to demystify the magic and history in the text. Further, I have adapted the content analysis method to analyze the textual evidences from the selected novel. The main finding exhibits that the novelist has amalgamated historical facts with magical elements like supernatural beings and happenings. Thus, the novel is an example of historical magical realism. This implies that only established beliefs and theories are not sufficient to judge the literary works rightly. Therefore, new lenses should be explored to enter into the world of fictional prose works as such.